If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2(3x + -10) = 23 Reorder the terms: 9x + -2(-10 + 3x) = 23 9x + (-10 * -2 + 3x * -2) = 23 9x + (20 + -6x) = 23 Reorder the terms: 20 + 9x + -6x = 23 Combine like terms: 9x + -6x = 3x 20 + 3x = 23 Solving 20 + 3x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 3x = 23 + -20 Combine like terms: 20 + -20 = 0 0 + 3x = 23 + -20 3x = 23 + -20 Combine like terms: 23 + -20 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| -2y=11-6 | | 2/3x−1/5x=x−1 | | Y=5(15)+b | | -17x-141=-11x-93 | | (b-25)(b+16)=0 | | Y=-.2x+6 | | 16x+208=8x+136 | | 25y^2+110y+121= | | 0(-5/3) | | 0.09xX=59.71 | | -10x+26=-5x+16 | | ln(x+900)=x^2 | | -21x+89=-13x+57 | | 3x-16=37 | | 15(x)=-4.9x^2+10x+40 | | 3/1=2/x | | f(2)=-2x^2-5x-6 | | -10=-7+3y | | 5x^4+15x^2-20=0 | | 1/8=x/2 | | 5x-7=-9 | | 9x-17=5x-9 | | 3x+4+5=35 | | x/15=3/9 | | -19x+122=-12x+73 | | y-7=5(7-10) | | 3p^3+9p^2-210p=0 | | x-4=15.5 | | 10+6=10 | | (2x-20)(x)=5400 | | c+15=49 | | x-8=-0.35 |